Analisis Kesalahan Siswa Dalam Menyelesaikan Soal-Soal Bangun Ruang Prisma Ditinjau Dari Gaya Belajar Siswa Kelas VII C SMPN 1 Mojogedang - lestari, Indra; Afghohani , Afif; Farahsanti, Isna (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The purpose of this study is to find out how students' errors in solving prism space building problems are viewed from the learning style of students in class VII C SMPN 1 Mojogedang.The research used descriptive qualitative research methods. The subjects in the study were students of class VII C SMPN 1 Mojogedang in the 2023/2024 school year. The object in this study is student errors in solving problems in terms of learning styles. Data collection techniques using questionnaires, tests, and interviews. The data validity technique uses method triangulation.  The conclusion of this study is the types of errors made by students in solving prism space building problems from the four learning styles above, it is found that students with visual styles make more mistakes in the transformation and process skill steps than other types of errors. Students with auditory learning styles also make more transformation, process skill and econding errors than other types of errors. Students with kinesthetic learning style only made errors in the encoding step. Meanwhile, students with combined learning styles made more errors in transformation, comprehension, process skills and encoding.